2019
DOI: 10.3390/acoustics1020019
|View full text |Cite
|
Sign up to set email alerts
|

Plate-Type Acoustic Metamaterials: Experimental Evaluation of a Modular Large-Scale Design for Low-Frequency Noise Control

Abstract: For industrial applications, the scalability of a finalised design is an important factor to consider. The scaling process of typical membrane-type acoustic metamaterials may pose manufacturing challenges such as stress uniformity of the membrane and spatial consistency of the platelet. These challenges could be addressed by plate-type acoustic metamaterials with an internal tonraum resonator. By adopting the concept of modularity in a large-scale design (or meta-panel), the acoustical performance of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Recently researchers have tried to address these challenges by replacing the elastic membrane with a stiff thin polymeric plate [55][56][57]. Ang et al [58] reported a large-scale plate type acoustic metamaterial for low-frequency noise control. The structure consists of two Mylar thin plate sheets and an internal tonraum resonator, assembled with two rigid outer frames.…”
Section: Acoustic Metamaterials As Sound Barriersmentioning
confidence: 99%
“…Recently researchers have tried to address these challenges by replacing the elastic membrane with a stiff thin polymeric plate [55][56][57]. Ang et al [58] reported a large-scale plate type acoustic metamaterial for low-frequency noise control. The structure consists of two Mylar thin plate sheets and an internal tonraum resonator, assembled with two rigid outer frames.…”
Section: Acoustic Metamaterials As Sound Barriersmentioning
confidence: 99%
“…The teetertotter-style microphone primarily operates within two resonant frequencies (two vibration modes) and their adjacent bands, thus restricting the sensor’s working bandwidth (usually <1 kHz). Considering the fact that signals below 1 kHz are crucial for speech applications and environmental noise localization [ 71 ]. As illustrated in Figure 12 , Zhang et al [ 72 ] achieved low-frequency applications at 500 Hz and 2 kHz by adjusting the central axis position of the device to modify resonant frequencies, and they utilized piezoelectric detection and capacitive auxiliary detection.…”
Section: Denoising Techniques For High-performance Mems Microphonesmentioning
confidence: 99%